2014
DOI: 10.1159/000358008
|View full text |Cite
|
Sign up to set email alerts
|

Are Newly Discovered Drivers of Immune-Mediated Skin Disorders Expressed in Normal Skin Regenerating from Standardized Surface Injury?

Abstract: Background: In healthy skin, tape stripping induces a transient wave of histological changes resembling immune-mediated skin diseases, such as psoriasis. The response to surface trauma may harbor mechanisms which are also relevant to the development of Koebner-positive skin disorders. However, studies on newly discovered drivers of inflammation in regenerative skin are lacking. Methods: The course of epidermal proliferation and keratinization as well as key representatives of innate and acquired immunity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…Previous observations [7] have shown that neutrophils are the main infiltrating cells in exudates formed after tape stripping and that the proportions of neutrophils to other leukocytes decrease with time after challenge; therefore, as the measurement in our study was 22-24 h post challenge, neutrophil numbers would be expected to be decreasing and this might be reflected in the lack of transcriptional changes in MPO. Other studies have also identified an important role for innate immune cells in response to tape stripping and these changes were observed within the dermal compartment of the skin [14]. CLEC4C was the other inflammatory cell marker up regulated after tape stripping in this study, indicating an increase in PDCs.…”
Section: Discussionsupporting
confidence: 69%
“…Previous observations [7] have shown that neutrophils are the main infiltrating cells in exudates formed after tape stripping and that the proportions of neutrophils to other leukocytes decrease with time after challenge; therefore, as the measurement in our study was 22-24 h post challenge, neutrophil numbers would be expected to be decreasing and this might be reflected in the lack of transcriptional changes in MPO. Other studies have also identified an important role for innate immune cells in response to tape stripping and these changes were observed within the dermal compartment of the skin [14]. CLEC4C was the other inflammatory cell marker up regulated after tape stripping in this study, indicating an increase in PDCs.…”
Section: Discussionsupporting
confidence: 69%
“…4,5 Koebnerization as an immune-mediated response has been studied, and levels of elastase-positive and interleukin-17-positive cells have been found to rise rapidly, whereas Tbetpositive cells increase gradually, peaking after other cell levels decrease when a skin injury occurs. 6 The therapeutic approach commonly taken to eliminate blood heat and blood stasis is ultimately to activate the blood through cupping. 2 The general method of cupping therapy requires a plastic or glass bell-shaped or spherical cup, 1 to 3 inches in diameter, to be placed on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…No clinical signs of irritation were visible at time points later than 1 h. On the other hand, the lack of activation of Langerhans cells in the epidermis and of influx of T cells in the dermis, evidenced by the unchanged numbers of CD1a- and CD3-positive cells, respectively, confirms that this model (at least with the parameters chosen in this study) is not suitable for studying key mediators of adaptive immunity activated by sustained inflammation. For studying these mediators, other in vivo models such as tape stripping and application of leukotriene B 4 would be more appropriate [3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the SC as skin barrier depends on the interplay of several factors, including the process of proliferation of keratinocytes from the basal layer and their gradual differentiation to corneocytes across the epidermis. Upon disruption of the SC, the release of mediators from keratinocytes, including several interleukins and chemokines [2], prompts the onset of an inflammatory response, resulting in a transient infiltrate of immune cells in the dermis, and hyperproliferation and abnormal differentiation in the epidermis [3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation